[Des]emaranhando a docência entre infância[s], escola e inventividade - Uecker, Taciana (2024)
This thesis is a bet on teaching, which can be extended to any teaching, but especially teaching for/with children. By problematizing teaching, I tried to come up with a thesis based on the questions: How can we think about teaching together with three threads: childhood, school and inventiveness? How do these threads become power to produce other relationships with children and inspire [other] teachers? In view of these questions, the objective: to problematize teaching by being a teacher for/with childhoods. In order to carry out the research, I produced a collection of snapshots that are part of my teaching experience with children and that make it teaching, experience, possibility and invention. Methodologically with a [dis]tangle of threads [words] to think about the in-between. Childhood, school and inventiveness, which, like threads, took center stage in the [dis]entanglement. I wrote this as a teacher-researcher in the making, who in [un]tangling seeks to avoid knots in order to bet on ties that can be unmade/re-made as many times as possible and necessary. In this way, the experience of teaching makes it possible to [dis]entangle other modes of teacher constitution when childhood [infanciar] and inventiveness move through an action of [being] teaching, which puts into operation a teacher function and the production of the school as territory[s] of inventiveness and experience.